Is Thoracic Radiotherapy an Absolute Contraindication for Treatment of Lung Cancer Patients With Interstitial Lung Disease? A Systematic Review. Issue 12 (December 2022) - Saha, A.; Dickinson, P.; Shrimali, R.K.; Salem, A.; Agarwal, S.
Abstract: Thoracic radiotherapy decisions in patients with interstitial lung disease (ILD) are complex due to concerns about severe or even fatal radiation pneumonitis. This systematic review analysed the published evidence regarding the incidence of radiation pneumonitis and mortality after thoracic radiotherapy and investigated clinical and dosimetric predictors of radiation pneumonitis in lung cancer patients with ILD. A systematic search was carried out in PubMed, Medline, Embase and the Cochrane database for articles published between January 2000 and April 2021. Two authors independently screened eligible studies that met our predefined criteria. Studies were assessed for design and quality and a qualitative data synthesis was carried out. The search strategy resulted in 1750 articles. After two rounds of screening, 24 publications were included. The median overall incidence of grade ≥3 radiation pneumonitis was 19.7% (range 8–46%). The incidence was greater in conventional radical radiotherapy-treated patients (median 31.8%) compared with particle beam therapy- or stereotactic ablative radiotherapy-treated patients (median 12.5%). The median rate of grade 5 radiation pneumonitis was 11.9% (range 0–60%). The presence of ILD was an independent predictor of severe radiation pneumonitis. Severe radiation pneumonitis was more common in the presence of usual interstitial pneumonia (UIP) pattern or idiopathic pulmonary fibrosis (IPF) than non-UIP or non-IPF subtype. Several other clinical predictors were reported in the literature. V5, V10, V20 and mean lung dose were the most common dosimetric predictors for severe radiation pneumonitis, often with stricter dose constraints than conventionally used. Patients with lung cancer associated with ILD had a poorer overall survival compared with patients without ILD. In conclusion, patients with lung cancer associated with ILD have a poor prognosis. They are at high risk of severe and even fatal radiation pneumonitis. Careful patient selection is necessary, appropriate high-risk consenting and strict lung dose-volume constraints should be used, if these patients are to be treated with thoracic radiotherapy. Highlights: Patients with lung cancer associated with ILD have a poor prognosis. They are at increased risk of severe and even fatal radiation pneumonitis. Patients must be counselled and appropriately consented regarding the increased risks when planning thoracic radiotherapy. Careful patient selection & strict lung dose volume constraints should be chosen if treated with thoracic radiotherapy.